Unusual Presentation of Rare Case of Papillary Adenofibroma of Cervix in a Young Woman - H. Mahesha Navada; B. Poornima Ramachandra Bhat; Gayatri Ramani; R. Rohan Chandra Gatty; C. S. Jayaprakash (Case Reports in Oncological Medicine)
Adenofibroma is an extremely rare benign biphasic neoplasm that is classified into the mixed epithelial and mesenchymal tumor group. These tumors tend to occur in postmenopausal and elderly women. We report the case of a large polypoidal mass per vagina occupying the whole pelvis in a young woman. Preoperative biopsy showed benign epithelial and mullerian mesenchymal components suggestive of mullerian adenofibroma. Total hysterectomy with bilateral salpingectomy was done. The diagnosis of papillary adenofibroma of cervix was made. The total surgery assured complete excision and permitted adequate sampling to exclude malignancy.